God’s Mercy is Not Limited to Arabic Speakers: Reading Intellectual Biography of Muhammad Salih Darat and His Pegon Islamic Texts - Umam, Saiful (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2013)
Muhammad Salih Darat is a Javanese ulama who is known for his Pegon Islamic texts—texts on Islamic knowledge written in Arabic script but using Javanese language. He did that after he learned various branches of Islamic knowledge with a number of respected ulama both in Java and Mecca. The significance of his works lay not only on the fact that he delineates Islamic knowledge of theology (tawḥīd), Islamic jurisprudence (fiqh), Islamic mysticism (taṣawwuf) and exegesis of the Qur’an (tafsīr) in local Javanese language but also on his insistence and defense that such texts are as authoritative as Arabic ones. Salih argues that to be a good Muslim and to receive God’s mercy is not conditional on one’s ability to speak and understand Arabic but on one’s observance of religious obligations with sufficient knowledge that one acquires from authoritative Islamic texts in any language.DOI: 10.15408/sdi.v20i2.388